AN ANALYSIS OF THE READINESS OF LECTURERS AND STUDENTS OF AL-QOLAM ISLAMIC INSTITUTE TO CHALLENGE THE INDUSTRIAL REVOLUTION 4.0 - Beny Hamdani; Kholifatul Handayani; Budik Kusworo (LP3M Universitas Islam Zainul Hasan Genggong, 2022)
ABSTRACT The purpose of this study was to determine the application of the industrial revolution 4.0 carried out in teaching and learning activities and to find out what challenges were faced by students of the Al-Qolam Islamic Institute of Malang. This research uses descriptive qualitative research. The subjects of this study were 7 lecturers and 12 students of the Tarbiyah Faculty of IAI Al-Qolam Malang. The data was taken from a questionnaire consisting of 8 questions with 2 choices, namely no and yes to determine the readiness of lecturers and students in facing the challenges of the industrial revolution 4.0. Based on the results of the study, it can be said that lecturers have a positive view of lecturers and students in facing the challenges of industry 4.0 at the Al-Qolam Islamic Institute. However, there are still obstacles and challenges faced by lecturers and students in learning in the era of the industrial revolution 4.0 at the Al-Qolam Islamic Institute. Keywords: Industrial Revolution 4.0, Readiness, Obstacles, Challenges ABSTRACT The purpose of this study was to determine the application of the industrial revolution 4.0 carried out in teaching and learning activities and to find out what challenges were faced by students of the Al-Qolam Islamic Institute of Malang. This research uses descriptive qualitative research. The subjects of this study were 7 lecturers and 12 students of the Tarbiyah Faculty of IAI Al-Qolam Malang. The data was taken from a questionnaire consisting of 8 questions with 2 choices, namely no and yes to determine the readiness of lecturers and students in facing the challenges of the industrial revolution 4.0. Based on the results of the study, it can be said that lecturers have a positive view of lecturers and students in facing the challenges of industry 4.0 at the Al-Qolam Islamic Institute. However, there are still obstacles and challenges faced by lecturers and students in learning in the era of the industrial revolution 4.0 at the Al-Qolam Islamic Institute. Keywords: Industrial Revolution 4.0, Readiness, Obstacles, Challenges